Responsibility for leadership in the Peace Agreement signed by the Colombian Government and the FARC-EP: an analysis based on the Bemba case of the International Criminal Court (2019)
This article discusses the rules on command responsibility issued within the implementation of the Peace Agreement between the Colombian Government and the guerrilla group FARC-EP. The objective is to analyse the meaning of those rules, considering the ju